Long-term aircraft maintenance scheduling for an aircraft maintenance centre: a case study. (6th November 2008) - Yan, Shangyao; Chen, Chun-Ying; Yuan, Chun-Ying
Traditionally, long-term aircraft maintenance scheduling is not only time-consuming but often ineffective. In this study, we develop a long-term aircraft maintenance scheduling model that can be used to perform this function for the aircraft preventive/predictive maintenance. The model is formulated as a multiple objective zero-one integer program. To find non-dominated solutions, the weighting method, coupled with the mathematical programming solver, CPLEX, is applied to solve the model. Finally, we perform a case study using real operating data from an aircraft maintenance centre in a major Taiwan airport. The results show that the model could be a useful planning tool.